Kajian Pemberian ASI Eksklusif Dan Pengaturan Pola Makan Terhadap Kejadian Stunting Pada Anak Umur 24 – 59 Bulan Bulan Di Wilayah Kerja Puskesmas Muncak Kabau - Jusmawati; Ayu Mislena (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
Background: The incidence of stunting among children aged 24-59 months in the Muncak Kabau Community Health Center working area occurs due to a lack of knowledge among mothers and the community about the benefits of exclusive breastfeeding and providing a good diet for toddlers and their children.Purpose of writing: To find out the knowledge of mothers and the community about exclusive breastfeeding and dietary regulation for children aged 24-59 months (2-5 years).Research Method: The independent and dependent variables of the sample are mothers who have children aged 2-5 years and the educational history of mothers who are at the UPTD Puskesmas Muncak Kabau, Buay Pemua Bangsa Raja District. East Ogan Komering Ulu Regency. Research Results: From the results of research, education is also consistent according to researchers, where low education (SD, SLTP) has less knowledge and insight, so they do not understand what stunting is in toddlers, so many toddlers are stunted, on the contrary, secondary education (Senior High School) and higher education (Academy , Higher Education) have better knowledge and insight, so that they understand what stunting symptoms and consequences are, so that their children under five are not stunted. Conclusions : There is a significant relationship between exclusive breastfeeding, diet, maternal education, maternal age, maternal occupation and stunting in toddlers.